Theories of Change: Modest radicalism or passive revolution? - Lane, Richard (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
In 2013, CCAFS began to experiment with a Theory of Change (ToC) approach to planning, monitoring and evaluation. An initial pilot phase then lead to ToC being adopted throughout the CRP. After outlining the general approach to ToC and their specific usage in CCAFS, this paper re-conceptualises and broadly problematises the ToCs approach in order highlight its potential or otherwise to enable transformative change in order to ask: what kind of future is imagined? What kind of transformation is made possible? What kind of knowledge and learning is enabled? What kind of actors are produced?